Parental substance use and child reward-driven eating behaviors. (1st January 2020) - Cummings, Jenna R.; Lumeng, Julie C.; Miller, Alison L.; Hyde, Luke W.; Siada, Ruby; Gearhardt, Ashley N.
Abstract: Family history of substance use is a well-established risk factor for greater substance use in adolescence and adulthood. The biological vulnerability hypothesis proposes that family history of substance use might also confer risk for obesogenic eating behavior because of similar rewarding characteristics between substances and certain foods (e.g., processed foods high in refined carbohydrates and fat). Indeed, preliminary research shows that family history of substance use is linked with sweet liking and obesity in adults; however, it is unknown whether this factor is linked to eating behavior earlier in development. The present study ( n  = 52) tested the association of severity of parental nicotine dependence and alcohol use (drinking frequency, drinking quantity, binge drinking, and number of annual drinks consumed) with two types of child [ M age  = 10.18 (0.83) years] eating behavior: homeostatic eating behavior, or eating regulated by internal satiety cues, and reward-driven eating behavior, or eating motivated by pleasure. Results indicated that—over and above the influence of child age, child biological sex, and family income—more severe parental nicotine dependence and frequent and/or heavy, frequent parental alcohol use were associated with significantly greater child reward-driven eating behaviors as indexed by the Food Responsiveness and Enjoyment of Food subscales on the Child Eating Behavior Questionnaire. Parental substance use was not associated with child homeostatic eating behavior as indexed by the Satiety Responsiveness subscale. Family history of substance use may be an important transdiagnostic risk factor that identifies children at risk for obesogenic, reward-driven eating behaviors.